Peningkatan Kepuasan Mahasiswa Melalui Kualitas Jasa Pendidikan: Studi Pada Mahasiswa di STIE Indonesia Banking School - Wasi Bagasworo; Santi Rimadias (Indonesia Banking School, 2014)
This research discusses the service quality through service performance affect customer satisfaction at STIE Indonesia Banking School (IBS). In this study, the variable of the service performance is measured through three dimensions: interaction quality, environmentalquality and quality of results. Each of these dimensions will be partially tested on how it affects customer satisfaction. In addition, this study also wanted to know which the most influential dimension to customer satisfaction. The research sample was 214 students who studied at least one year in STIE Indonesia Banking School. The observations will be analyzed using the Statistical Product and Service Solutions (SPSS). The results from the study showed that the three dimension of service performance have a strong significant effect on customer satisfaction